Reversal of Spironolactone-Induced Gynecomastia: : A Review and Case Report of Spironolactone-Induced Gynecomastia (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Pulmonology; Research